A Kolozsvári Egyetem 1872-7919 közötti története, levéltári és könyvtári dokumentumainak feltárása és digitalizálása - Vajda, Tamás (Gerundium, 2017)
The History of the University of Kolozsvár in the Years 1872 to 1919: The Exploration and the Digitalization of its Archival Material and Library Documents. The research program discussed here was launched by the Archives of the University of Szeged in the spring of 2014, and its major objective has been the exploration of archival material and library documents from the various collections to be found in Kolozsvár, Marosvásárhely and Hungary. Additional aims include the actual digitalization of documents, making the digitalized stock available primarily for university students and for the teaching staff, as well as the promotion of historical research. The head of the program provides here a detailed account of the project’s justifications, preparation, the hitherto covered stages, the execution of source collection and digital photography, as well as the program’s infrastructural and personal demands. Mention is also made of making the project results available, as well as the possibilities of utilization. The tasks of the near future are also treated.